2005
DOI: 10.1080/10601320500246602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Liquid Crystalline Behavior of Random Copolymer of Poly(ethylene oxide) Macromonomer and Liquid Crystalline Monomer by the Photon Transmission Technique

Abstract: Random copolymers of poly(ethylene oxide) macromonomer with p-vinylbenzyl end-functional group (PEOVB) and liquid crystalline monomer, namely 6-(4-cyanobiphenyl-4 0 -oxy)hexyl acrylate (COA), were prepared by conventional free radical polymerization. A living anionic polymerization technique was employed for the synthesis of PEO macromonomers bearing p-vinylbenzyl moiety at one end. The photon transmission method was also applied to study the phase transitions of COA monomer and its random copolymer with PEO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…After the block formation, PVEC block can readily be crosslinked by photochemical means by intermolecular dimerization of the cinnamate groups (Scheme 1). We have recently described a new synthetic strategy for the preparation of heterofunctional macromonomers carrying methacryloyl group at one end, and dimethyl amino, thiophene, styryl and vinyl ether functional groups at the other end [13][14][15][16][17][18][19]. In this strategy, first anionic polymerization of ethylene oxide (EO) was initiated with functional potassium alcoholates, and then living ends were reacted with methacryloyl chloride.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the block formation, PVEC block can readily be crosslinked by photochemical means by intermolecular dimerization of the cinnamate groups (Scheme 1). We have recently described a new synthetic strategy for the preparation of heterofunctional macromonomers carrying methacryloyl group at one end, and dimethyl amino, thiophene, styryl and vinyl ether functional groups at the other end [13][14][15][16][17][18][19]. In this strategy, first anionic polymerization of ethylene oxide (EO) was initiated with functional potassium alcoholates, and then living ends were reacted with methacryloyl chloride.…”
Section: Introductionmentioning
confidence: 99%
“…In this strategy, first anionic polymerization of ethylene oxide (EO) was initiated with functional potassium alcoholates, and then living ends were reacted with methacryloyl chloride. These macromonomers were further utilized in various macromolecular architectures via concurrent or selective thermal free radical [19,20], oxidative [15] and photoinitiated free radical [13,21,22] and cationic polymerization [21] methods. It was also shown that graft co-polymers with completely and perfectly alternating hydrophilic side-chains can be prepared by charge-transfer-polymerization of the styrene functional macromonomers with phenyl maleimide [20].…”
Section: Introductionmentioning
confidence: 99%